Engineers and management : international comparisons (London ; New York : Routledge, 1992)
This book presents: Engineers and management in comparative perspectives; Wheels within wheels: predicting and accounting for fashionable alternatives to engineering; The engineering dimension and the management education movement; ...
Keywords: Economics; Management; Engineering; Engineering -- Management